3D meso-scale modelling of concrete material in spall tests - Chen, G.; Hao, Yifei; Hao, Hong (Springer Netherlands, 2015)
Tensile strength is one of the key factors of concrete material that need be accurately defined in analysis of concrete structures subjected to high-speed impact loads. Dynamic tensile strength of concrete material is usually obtained by conducting laboratory tests such as direct tensile test, Brazilian splitting test and spall test. Concrete is a heterogeneous material with different components, but is conventionally assumed to be homogeneous, i.e., cement mortar only, in most previous experimental or numerical studies. The aggregates in concrete material are usually neglected owing to testing limitation and numerical simplification. It has been well acknowledged that neglecting coarse aggregates might not necessarily give accurate concrete dynamic material properties. In the present study, a 3D meso-scale model of concrete specimen with consideration of cement mortar and aggregates is developed to simulate spall tests and investigate the behaviour of concrete material under high strain rate. The commercial software LS-DYNA is used to perform the numerical simulations of spall tests. The mesh size sensitivity is examined by conducting mesh convergence tests. The reliability of the numerical model in simulating the spall tests is verified by comparing the numerical results with the experimental data from the literature. The influence of coarse aggregates on the experimental test results is studied. The wave attenuation in concrete specimen is analysed, and empirical equations are proposed for quick assessment of the test data to determine the true dynamic tensile strength of concrete material. The contributions of aggregates to dynamic strength in spall tests are quantified for modifying the test results based on mortar material in the literature.